O cuidado na morte: as concepções da equipe da hospedaria de cuidados paliativos do Hospital do Servidor Público Municipal - HSPM - Iha, Vera Lucia (2011)
The purpose of this study is to examine the provision of palliative care services at the Palliative Care Unit of the Hospital do Servidor Público, in the city of São Paulo, Brazil. The study aimed at identifying and analyzing the meaning of this service to the supervisor and his team of professionals at the Palliative Care Unit. For the purpose of this study, we assumed that the palliative care services at the Unit have been delivered in a gradual and systematic mannerwith their challenges and opportunities.The methodology comprised bibliographical and document research, as well as qualitative field work. We used the technique of semi-structured interviews with 10 subjects.For analysis of data, the content analysis technique was used. The reference concepts chosen were Death, Care, Palliative Care, Humanization, and Multiprofessional Team. Results showed that the philosophy behind palliative care within the hospital scope includes some significant limitations and institutional challenges for the effective delivery of services on a daily basis. However, the professional practices adopted by the Palliative Care Unit team at the Hospital do Servidor Público have been consolidated into a streamlined process that includes full health care coverage to users and their families, interdisciplinary activities and stimulus to professional empowerment and autonomy in the delivery of services